Exposing the Specific Roles of the Invariant Chain Isoforms in Shaping the MHC Class II Peptidome - Fortin, Jean-Simon; Cloutier, Maryse; Thibodeau, Jacques (Frontiers in Immunology, 2013)
The peptide repertoire (peptidome) associated with MHC class II molecules (MHCIIs) is influenced by the polymorphic nature of the peptide binding groove but also by cell-intrinsic factors. The invariant chain (Ii) chaperones MHCIIs, affecting their folding and trafficking. Recent discoveries relating to Ii functions have provided insights as to how it edits the MHCII peptidome. In humans, the Ii gene encodes four different isoforms for which structure-function analyses have highlighted common properties but also some non-redundant roles. Another layer of complexity arises from the fact that Ii heterotrimerizes, a characteristic that has the potential to affect the maturation of associated MHCIIs in many different ways, depending on the isoform combinations. Here, we emphasize the peptide editing properties of Ii and discuss the impact of the various isoforms on the MHCII peptidome.